Programa de tutoría socioemocional en el mejoramiento de la convivencia escolar de los estudiantes del tercer grado de secundaria de la Institución Educativa Colegio Nacional Iquitos distrito de San Juan Bautista 2024 - García Pérez, Kelly Judiksa (2025)
The research evaluated the impact of the socio-emotional tutoring program on the improvement of school coexistence among third-year high school students at the National College of Iquitos in the San Juan Bautista district in 2024. An evaluative study with cross-sectional analysis and a quasi-experimental design was employed. The sample included 70 students, divided into an experimental group of 36 students and a control group of 34 students. A validated questionnaire was used to collect data. The results showed a positive and significant impact on the experimental group (mean = 71.975) compared to the control group (mean = 64.608). Tutoring improved school coexistence, self care, inclusion, democratic participation, and discipline based on respect. The students developed communication skills, teamwork, and conflict resolution. They also practiced self-awareness and emotional regulation, which strengthened their interpersonal relationships and academic performance. These findings highlight the importance of socio-emotional interventions to foster a more inclusive and equitable educational environment, promoting the personal and social growth of students.